OsDMI3‐mediated OsUXS3 phosphorylation improves oxidative stress tolerance by modulating OsCATB protein abundance in rice. Issue 5 (29th April 2022) - Ni, Lan; Wang, Qingwen; Chen, Chao; Wang, Shuang; Shen, Tao; Jiang, Jingjing; Cui, Zhenzhen; Li, Kaiyue; Yang, Qiqing; Jiang, Mingyi
Abstract: Calcium (Ca 2+ )/calmodulin (CaM)‐dependent protein kinase (CCaMK) is an important positive regulator of antioxidant defenses and tolerance against oxidative stress. However, the underlying molecular mechanisms are largely unknown. Here, we report that the rice ( Oryza sativa ) CCaMK (OsDMI3) physically interacts with and phosphorylates OsUXS3, a cytosol‐localized UDP‐xylose synthase. Genetic and biochemical evidence demonstrated that OsUXS3 acts downstream of OsDMI3 to enhance the oxidative stress tolerance conferred by higher catalase (CAT) activity. Indeed, OsUXS3 interacted with CAT isozyme B (OsCATB), and this interaction was required to increase OsCATB protein abundance under oxidative stress conditions. Furthermore, we showed that OsDMI3 phosphorylates OsUXS3 on residue Ser‐245, thereby further promoting the interaction between OsUXS3 and OsCATB. Our results indicate that OsDMI3 promotes the association of OsUXS3 with OsCATB to enhance CAT activity under oxidative stress. These findings reveal OsUXS3 as a direct target of OsDMI3 and demonstrate its involvement in antioxidant defense. Abstract : Ca 2+ /calmodulin‐dependent protein kinase (CCaMK) plays important roles in scavenging reactive oxygen species. A rice CCaMK phosphorylates a cytosolic‐localized UDP‐xylose synthase, which can increase antioxidant enzymes, such as catalase, thus protecting plant cells by scavenging reactive oxygen species.